A taxonomic foundation for evidence-based research on employee performance management - Posthuma, Richard A.; Charles Campion, Michael; Campion, Michael A. (European journal of work and organizational psychology, 2018)
This study presents a taxonomic foundation for research on employee performance management practices based on a comprehensive review of the literature (198 articles and book chapters). The taxonomy consists of 50 practices organized within seven topic categories, including an evaluation of the amount of research evidence supporting each practice. This taxonomic foundation facilitates the aggregation, integration, interpretation, and explanation of performance management research based on a role-theoretic perspective derived from the behavioural approach to strategic human resource management. The proposed direct-linkage path model shows how this taxonomic foundation ties performance management practices to behaviours and results. We build on this Practice - Behaviour - Results (PBR) critical path model with moderators and mediators based on cognitive and social factors identified in the extensive previous research. This PBR model provides a foundation for orderly and structured growth for future research that will enhance the connection between research and improved organizational practices in performance management, as well as a guide to best practices in performance management.